New species and new records of Brueelia Kéler, 1936 (Phthiraptera: Ischnocera) from South Africa - Gustafsson, Daniel R.; Grossi, Alexandra A.; Halajian, Ali; Engelbrecht, Derek (Zootaxa, 2024)
Three species of the genus Brueelia Kéler, 1936 are reported from South Africa for the first time: Brueelia cyclothorax (Burmeister, 1838) ex Passer domesticus (Linnaeus, 1758), Brueelia queleae Sychra & Barlev [in Sychra et al.], 2010a ex Quelea quelea lathami (Smith, 1836), and Brueelia coryliventer Gustafsson & Bush, 2015, ex Creatophora cinerea (Meuschen, 1787). In addition, two new species of Brueelia are described from South African ploceids: Brueelia oschadlei n. sp. ex Ploceus capensis (Linnaeus, 1766), and Brueelia inusta n. sp. ex Ploceus velatus tahatali Smith, 1836. Also, we discuss the “African pied Brueelia” species-group—to which the two new species belong—in particular the variation in pigmentation patterns on the subgenital plates of both sexes.